The influence of parents' roles and motivation on student achievement in buddhist education subjects at Bodhisattva elementary school Bandar Lampung - Anggi Tri Prameswari; Hesti Sadtyadi; Mirrah Megha Singamurti (Universitas Ahmad Dahlan, 2022)
This study aims to determine the effect of the role of parents on student achievement in the subject of Buddhist Education, to determine the effect of learning motivation on student achievement, to determine the effect of the role of parents and motivation on student achievement at SDS Bodhisattva in Buddhist Education Subjects. The results of the study 1) the results of the significance of 0.038 > 0.05 and t count 1.815 > t table 2.03011 so that Ho2 is accepted and Ha2 is rejected, that is, there is an influence of 41.8% on the role of parents on learning achievement. 2) of 0.033 > 0.05 and t count 1.978 > t table 2.03011 so that Ho2 is accepted and Ha2 is rejected, that is, there is an influence of 41.8% motivation on student achievement. 3) the significance value is 0.616 < 0.05 and learning achievement is 0.616 < 0.05 and the calculated F value is 3.078 < F table 2.465809. It can be concluded that Ha3 is accepted as having an effect so that 19.9% the role of parents and motivation on student achievement. Based on the results of the study, it can be concluded that there is a significant influence between the role of parents, motivation and learning achievement in grades IV, V and VI in Buddhist education subjects at SDS Bodhisattva Bandar Lampung